Application of Linear Congruential Generator (LCG) Algorithm in Android Based Mathematics Education Game - Khalis Abi Perbawa; Diana Diana (Jurnal Komputer, Informasi dan Teknologi, 2022)
Mathematics is a lesson learned from elementary, junior high, high school to tertiary levels. Many students have a negative attitude towards mathematics because mathematics is considered very boring and is considered the most difficult subject among other subjects, this can cause students to find it difficult to learn mathematics. Of course, the very rapid development of technology cannot be separated from the role of mathematics. Mathematics is a science that is the basis for the development of modern technology. Apart from that, mathematics also has an important role in various aspects of life. Solutions to help students understand mathematics, including through educational games. Educational games are techniques that can motivate and provide a better learning experience. The Linear Congruential Generator (LCG) algorithm is a random number generation method that is widely used in computer programs that utilize linear models. The results showed that the Linear Congruential Generator (LCG) method in the mathematics education game was successfully applied. Based on the results of game testing using questionnaires to students, teachers, and the general public (student guardians), it was found that the application made was included in the "Very Good" category with an average result of 80.55%.